Development And Validation Of A Questionnaire To Assess Knowledge, Attitude And Confidence Regarding Cardiopulmonary Resuscitation Among Ambulance Drivers In Malaysia - Jamie Foong Siew Wei; Mohd Azmani bin Sahar; Ahmad Zulkarnain Ahmad Zahedi (Pharmascope Publications, 2024)
Indexed by Scopus